Animal Welfare: Focusing on the Future. By David J. Mellor and A.C. David Bayvel. OIE: Paris, France, 2014; 358 pp; €65.00; ISBN: 978-92-9044-929-4 - Donald M. Broom (Animals, 2014)
This book, which is a volume in an OIE series, describes much that is relevant to animal welfare, the chapters being in English with summaries or full text in French and Spanish. As with many reviews of our state of knowledge, many contributions to this volume draw on previous publications. For example, David Fraser’s excellent discussion of the globalization of farm animal welfare is explained at greater length in his 2008 paper [1] and book [2]. However, chapters on drivers of animal welfare policy in Africa, the Americas, the Far East and Australasia and the Middle East are amongst those that are novel. The description by Aidaros of Islamic teachings in relation to animal welfare is particularly welcome.[...]